Research Misconduct in Low- and Middle-Income Countries - Ana, Joseph (Public Library of Science, 2013)
As part of a cluster of articles critically reflecting on the theme of “no health without research,” Richard Smith and colleagues lay out what is currently known about research misconduct in low- and middle-income countries, summarizing some high profile cases and making suggestions on ways forward.